Vortex Assisted Liquid–Liquid Microextraction Using Triton X‐114 for Ultratrace Cadmium Prior to Analysis. Issue 8 (26th November 2013) - Khan, Sumaira; Yilmaz, Erkan; Kazi, Tasneem Gul; Soylak, Mustafa
Abstract : A vortex‐assisted liquid–liquid microextraction method coupled to micro‐sample injection flame atomic absorption spectrometry for cadmium (Cd) determination in water samples, phenomena was established through phase separation of ionic surfactant in aqueous samples. The ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate [C4 MIM][PF6 ] was used as an extractant, while using Triton X‐114 as dispersing medium. The chelate of Cd with ammonium pyrrolidinedithiocarbamate (APDC) was extracted into the fine droplets. The main factors affecting the recovery values of Cd, such as [C4 MIM][PF6 ], pH, TX‐114, concentration of APDC, centrifugation time and rate were investigated in detail. At optimum experimental values of significant variables, preconcentration factor of 20 was obtained. The validity of developed method was checked by Cd determination in certified reference material of water (TMDA‐54.4 fortified lake water) and the results were found good agreement with the certified values. The relative standard deviation was 4.2% for 100 µg Cd/L. The method was applied satisfactorily for the preconcentration of Cd in real samples. Abstract : The VALLME method coupled to microsample injection flame atomic absorption spectrometry for Cd determination in water samples was established. Ionic liquid physicochemical properties can be modified by addition of non‐ionic surfactants. Main factors affecting the recovery values of Cd were investigated. The RSD was 4.2% for 100 µg/L of Cd. The method was applied satisfactorily for the preconcentration of Cd in real samples.